“The ANC will rule until Jesus comes”: The determinants of loyalty, switching and exiting for the African National Congress in the 2019 elections - Jacobs, Edward Keenan (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.